(3GdefTBJ PGJ GdaQhYs - (3eMeO(B, (3eWQs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2003)
(3GdfXe GdeMGSHjI aj TQcGJ GdebGhdGJ(B- (3GdfXe GdeMGSHjI aj GdefTBJ PGJ GdGbSGe(B- (3GdfXe GdeMGSHjI aj GdefTBJ PGJ GdaQhY GdeMGSHI Yf GdHjY HGdJbSjW (B- (3GdeMGSHI Yf HVGYI GdGeGfI(B- (3GdfXe GdeMGSHjI aj GdafGOb(B- (3GdfXe GdeMGSHjI aj GdeSJTajGJ(B.s
(3GdeQGLY U(B.317s
Keywords: (3GdTQcGJ(B- (3GdeMGSHIs; (3GdeMGSHI GdNGUIs; (3GdfXe GdeMGSHjIs